Understanding The Value of Differences in Sociocultural Applications in Education Across 3 Generations - Nabillah, Nida; Hendariyunisha, Shifa; Wirza, Yanty (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This study discusses sociocultural applications in 3 generations. The purpose of this study is to discuss how 3 generations (X Y, Z) understand and learn about differences in sociocultural applications (informal (family), non-formal (environment), and formal (school). This research was conducted because of the increasing issue of bullying. The method used in this study is descriptive qualitative with data sources derived from sample interview techniques with 3 people from each generation, then analyzed how the 3 generations interpret the differences in the sociocultural application learning process found in the interview results. what was found was that the 3 generations were humans as creatures of collectivism, gaining understanding and learning through behaviorism, cognitivism, and constructivism, and lastly, looking at differences between multiculturalism and pluralism because Indonesia is a country full of diversity.